Unexpected Gallbladder Metastasis of Clear Cell Renal Carcinoma - Ian White; Shane Smith; Kamilia Rizkalla; Edward Davies (SAGE Publishing, 2019)
Renal cell carcinoma (RCC) commonly metastasizes to areas such as the lungs, liver, bone, brain, adrenals, and lymph nodes. We present a rare case of a 59-year-old female patient with RCC metastasis to the gallbladder. The patient had undergone right nephrectomy for RCC more than 6 years prior to the metastasis. During routine follow-up, a polypoid lesion of the gallbladder was identified. Laparoscopic cholecystectomy was performed, and pathologic examination of the specimen revealed metastatic RCC. The patient was completely asymptomatic, which reinforces the importance of postoperative follow-up. Renal cell carcinoma is one of the few common malignancies for which there is good evidence of survival benefit from surgical resection of the metastatic tumours.